2020
DOI: 10.1080/13685538.2020.1870038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standardversuspopulation-specific handgrip strength cut-off points in the detection of probable sarcopenia after launch of EWGSOP2

Abstract: Objective: We aimed to compare European Working Group on Sarcopenia in Older People (EWGSOP2)-suggested and population-specific handgrip strength (HGS) thresholds to detect probable sarcopenia and their associations with physical-performance measures and frailty. Methods: A retrospective cross-sectional observational-study included geriatrics outpatients applied to a university-hospital. HGS, timed up and go test (TUG), and usual gait speed (UGS) were assessed. Frailty was screened by FRAIL-scale. Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…Recent research found that the new cut-offs of HGS by EWGSOP2 identified very small percentage of the elderly with probable sarcopenia and may lead to underdiagnose sarcopenia. 37 In our study, the number of participants who were identified as low muscle strength was considerably lower with EWGOSP2-recommended (27/16 kg) cut-offs than with the EWGOSP-recommended (30/20 kg) cutoffs (1005 participants, 8.1% versus 2125 participants, 17.1%). To identify the probable sarcopenia in older adults and avoid underdiagnosis, we used cut-offs by EWGSOP (30/20 kg).…”
Section: Discussioncontrasting
confidence: 50%
“…Recent research found that the new cut-offs of HGS by EWGSOP2 identified very small percentage of the elderly with probable sarcopenia and may lead to underdiagnose sarcopenia. 37 In our study, the number of participants who were identified as low muscle strength was considerably lower with EWGOSP2-recommended (27/16 kg) cut-offs than with the EWGOSP-recommended (30/20 kg) cutoffs (1005 participants, 8.1% versus 2125 participants, 17.1%). To identify the probable sarcopenia in older adults and avoid underdiagnosis, we used cut-offs by EWGSOP (30/20 kg).…”
Section: Discussioncontrasting
confidence: 50%
“…However, our Spanish questionnaire did show good discrimination according to muscle function (muscle strength or physical performance). This suggests that quality of life, at least in our participants, is better correlated to muscle function than to muscle mass and emphasized the issues raised with measuring muscle mass and defining cut-off points [ 2 , 48 ]. Our cut-off point of SPPB ≤ 9 as an inclusion criterion is based on the design of the SPRINTT trial (based on the LIFE trial) [ 28 , 49 ] and SPPB < 8 as an indicator of low physical performance and sarcopenia severity according to the EWGSOP2 when we classified our participants according to their physical function.…”
Section: Discussionmentioning
confidence: 99%
“…El kavrama kuvveti ölçümü için Jamar® dijital el dinamometresi kullanılmıştır. Kas kuvveti ölçümleri Bahat ve arkadaşlarının Türkiye için belirlediği kesim noktaları değerlerine göre kıyaslanmıştır (22). Buna göre el kavrama kuvveti erkekler için <35 kg, kadınlar içinse <20 ise "yetersiz" olarak değerlendirilmiştir.…”
Section: çAlişma Di̇zayni Ve Protokolüunclassified